The Role of Islamic Financial Investment in Indonesia's Economic Growth in the Digital Era: An Analysis of Impacts and Challenges - Mubarak, Muhammad; Suriyati, Andi; Azwari, Peny Cahaya (The Future of Education Journal, 2025)
This study aims to analyze the impact of Islamic investment on economic growth in Indonesia. Islamic investment, based on Islamic principles such as the prohibition of usury and speculation, has grown significantly in recent years. This research uses a qualitative approach with secondary data from financial reports, economic statistics, and related studies. The results show that Islamic investment contributes positively to Indonesia’s economy, particularly through the Islamic financial sector and increased financial inclusion. Islamic investment instruments, such as sukuk and Islamic mutual funds, provide stable and sustainable financing alternatives. Sukuk, for instance, is used to finance infrastructure projects that support economic growth. Additionally, Islamic financial products expand access to finance for communities previously excluded from the conventional financial system. However, challenges such as low financial literacy on Islamic finance, limited Islamic financial products, and the need for stronger regulations must be addressed. Therefore, strengthening policies and supporting infrastructure is necessary to optimize the development of Islamic investment in Indonesia.